DEVELOPMENT OF SCIENCE STUDENT WORKSHEET BASED ON PROJECT BASED LEARNING MODEL TO IMPROVE COLLABORATION AND COMMUNICATION SKILLS OF JUNIOR HIGH SCHOOL STUDENT - Kartika Arum Sari; Zuhdan Kun Prasetyo; Widodo Setiyo Wibowo (Universitas Negeri Yogyakarta, 2017)
This research aims to (1) produce a reasonable science student worksheet to improve collaboration and communication skills of junior high school student, (2) • determine the student's collaboration skills training by the Wadi worksheet, (3) • determine the student's communication skils training by the Wadi worksheet, (4) • determine the student's response after using the worksheets. This research is R D with 4 D and models (Define, Design, Develop, and Disseminate). The instruments used in this research consisted of validation form of science student worksheet, the student's questionnaire response form, the form of learning process with project based learning models, self-just my assesment of collaboration skills, peer-just my assesment of collaboration skills, observation sheet of collaboration skills, and observation sheet of communication skills. The data were analyzed using qualitative and quantitative analysis. Qualitative analysis for the data of worksheet's validation and students's response. Quantitative analysis for collaboration skills training of self-just my assesment; Peer-just my assesment; and observation sheet data and communication skills training of observation sheet data that for both of them by percentage calculations-gain score calculation U Mann-Whitney, and for percentage of learning process. The result showed that (1) the worksheet that has produced was reasonable to improve collaboration and communication skills of junior high school student; (2) student's collaboration skills training have moderate categories, 31.54% from it is